PENGARUH KONSELING GIZI TERHADAP KEPATUHAN DIET PADA PENDERITA DIABETES MELLITUS DI RAWAT JALAN RSUD Dr. R. SOETIJONO BLORA - Lia Camelia Kusuma; Dyah Nur Subandriani; Arinthina Rahayuni (JURNAL RISET GIZI, 2016)
Background : Diabetes Mellitus is a degenerative disease, one of the cause is false meal system, such as high fat sugar,and also low fiber. Counseling is one of nutrition service which has a purpose to change knowledge,attitucle,and meal system based on patient’s necessary,so it can measure the diet obedience that has been decided. Patient’s obedience to nutrition’s principle and meal plan is one of obstacle for diabetes patient. Objective : Knowing the influence of nutrition counseling to diet’s obedience of Diabetes Mellitus Sufferer type 2 in progressive treatment in RSUD Dr.R.Soetijono Blora. Method : Quasi Experiment non randomizes and pretest postest’s plan. Sample interpretation by using purposive sampling technique,gaining sample of 20 respondent based on inclusive criteria. Data analysis uses statistic experiment of Mc Nemar test to analyze counseling to diet’s obedience. Result : No diversity of diet’s obedience before and after counseling to Diabetes Mellitus patient in RSUD Dr.R.Soetijono Blora (p=0,22) Conclusion : Diet’s obedience of Diabetes Mellitus patient is not different before and after counseling to Diabetes Mellitus patient in RSUD Dr.R.Soetijono Blora.